PERSEPSI ORANGTUA TERHADAP PENTINGNYA PERKEMBANGAN KOGNITIF ANAK USIA DINI PADA KELOMPOK BERMAIN KASIH BUNDA - Amiyati, Dewi Rara; Mutaqin, Moh. Fikri Tanzil; Risna, Inten (LPPM Universitas Bina Bangsa, 2024)
This research aims to determine parents' perceptions of the importance of early childhood cognitive development in the Mother's Love Play Group in increasing parents' awareness of the importance of early childhood cognitive development. The research method used is qualitative with a case study approach, involving interviews, observation and documentation to collect data. The main findings show that the perceptions of parents in the Kasih Bunda play group regarding the cognitive development of early childhood vary. Parents act as partners with teachers by repeating material taught at school and teaching values such as respect and religious knowledge. They also act as guardians by upholding justice, teaching responsibility, and forgiveness. As friends, parents accompany children when studying and eating, creating a comfortable environment for communication. As facilitators, parents fulfill their children's school needs such as study desks and stationery, which supports cognitive development. Parents in this group show great concern for their children's cognitive development, trying to provide the support and facilities necessary for their children's education so that they become individuals with good character and benefit society. However, factors such as limited parental time, heredity, environment, interests and talents and freedom. Suggestions for deepening knowledge about early childhood education, because this period is the ideal time to provide stimulation that supports optimal child development